Diversity and Conservation Knowledge of Chondrichthyans in Northern Coastal Areas of Central Java - Setiati, Ning; Peniati, Endah; Partaya, Partaya (Biosaintifika: Journal of Biology & Biology Education, 2018)
Northern coastal areas of Central Java potentially produces sharks and rays (Chondrichthyes) for dishes. However, lack of community understanding of protected species catchment affects the Chondrichthyans conservation management. This study aimed to identify of total Chondrichthyans that were captured by fisherman correlated to the conservation knowledge and action in northern coastal areas of Central Java. This research was conducted by using interview, and direct observation. Samples were collected in fish capture household places in Tegal, Pemalang, Pekalongan, Semarang, Pati, and identified in Animal Taxonomy Laboratory of Biology Department, Universitas Negeri Semarang. Data were analyzed using descriptive qualitative based on the morphology characteristic. This research found that every season, at least 1,106 individuals from 23 species of Rajiformis and Lamniformis (Chondrichthyes) orders was captured. This condition was aggravated with lack of access to information and low fishermanâ awareness of protected species. It was also found that shark and ray trading generates value chain in culinary business. It increases fish consumption demand that only can be provided by fish catchment from the ocean. The implication of species catchment is declining population of Chondrichthyes in Central Java north areas. Based on the research, a high demand and lack of access to information correlated with declining community awareness on conservation actions. this research adds more information as an effort to conserve shark and ray species based on problems faced by fishermen. The information is also able to be applied as a foundation to develop community based conservation action.